Объяснение:
2^x^2 *2^(x-1) < 2^(3(*x/3 +3)), 2^(x^2+x-1) < 2^(x+9) ( ^-знак степени)
x^2+x-1<x+9, x^2 -10<0, (x-V10)*(x+V10)<0, + + + + + (-V10) - - - - -- (V10) ,
ответ (-V10; V10) (V-корень)
Объяснение:
2^x^2 *2^(x-1) < 2^(3(*x/3 +3)), 2^(x^2+x-1) < 2^(x+9) ( ^-знак степени)
x^2+x-1<x+9, x^2 -10<0, (x-V10)*(x+V10)<0, + + + + + (-V10) - - - - -- (V10) ,
ответ (-V10; V10) (V-корень)
х^4-4х^2+4+3+х^2-11=0;
х^4-3х^2-4=0;
х^4-4х^2+х^2-4=0;
х^2(х^2-4)+(х^2-4)=0;
(х^2-4)(х^2+1)=0;
а) х^2=-1, не имеет смысла т.к. выражение в квадрате не может быть отрицательным;
б) х^2=4, извлекаем корень;
х1=2; х2=-2